PENGELOLAAN PEMBELAJARAN AKIDAH AKHLAK DI ERA REVOLUSI INDUSTRI 4.0 DI MA HIDAYATUL MUBTADIIN JATI AGUNG KABUPATEN LAMPUNG SELATAN TAHUN PELAJARAN 2023/2024 - ROHANA ZIO BASTIAN (UNISAN JURNAL, 2024)
Learning management is an effort carried out by teachers in learning activities or people who help them with the aim of ensuring optimal conditions of Moral Aqidah, so that the expected learning activities can be carried out. MA Hidayatul Mubtadiin Jati Agung is a madrasa under the auspices of the Ministry of Religion and implements learning management in the industrial era 4.0. After conducting observations, it was found that MA Hidayatul Mubtadiin Jati Agung in its implementation carried out management of Islamic religious education learning in the industrial era 4.0. This research aims to find out the problems of Aqidah Akhlak that are currently occurring and what the challenges of Aqidah Akhlak will be in the future. Then what is the solution for the world of Aqidah Akhlak so that it can compete and even become a reference in the implementation of education in Indonesia? The research method uses literature studies by collecting data from documentation using descriptive-analysis methods. The transformation of the Aqidah Akhlak is needed to bring out the crisis and problems, strengthening the Aqidah Akhlak institutions also needs attention, including strengthening the management of the Aqidah Akhlak, strengthening the leadership of Islamic education, and reforming educational policies, with the aim of forming a complete generation and superior human beings who are competitive namely, people who are creative, innovative, have character, are independent, love their country and are religious to face Era 4.0 where people are required to be fast, precise, effective and efficient. Keywords. Management of Moral Creed Learning, Industrial Era 4.0